Implementation of the Canadian Emergency Department Triage and Acuity Scale (CTAS) in an Urgent Care Center in Saudi Arabia - Arafat, Abdullah (Int J Emerg Med, 2016)
OBJECTIVES: The objectives of the study is to review and assess the implementation of the applied modified five-level triage and acuity scale triage system in AL-Yarmook Urgent Care Center (UCC), King Abdulaziz Residential City, Riyadh, Saudi Arabia. METHOD: An observational cross-sectional study was conducted, where a data collection sheet was designed and distributed to triage nurses. The data collection was done during the triage process and was directly observed by the co-investigator. The triage system was reviewed by measuring three time intervals as quality indicators: time before triage (TBT), time before being seen by physician (TBP), and total length of stay (TLS) taking in consideration the timing of presentation and the level of triage. RESULTS: A total of 187 patients visiting the UCC during December 2014 were included. There was an almost equal distribution of males 98 (52 %) and females 89 (48 %) with most of the patients being in the age group of 14 years and younger (n = 85, 46 %). The visits of the patients were classified according to the level of triage from patients to be seen immediately by the physician to those who had been triaged out. Overall, 173 patients (92.5 %) were seen by the physician in a timely manner according to triage guidelines, while 14 patients (7.5 %) were not. The mean time was 5.36 min in TBT, 22.6 min in TBP, and 59 min in TLS. The median time to be seen by the physician was significantly greater (p = 0.001) for the urgent cases on the weekends (25 min; IQR, 21,30) as compared to the weekdays (17 min; IQR, 14,21). Generally, the results did not show significant increases in TBT, TBP, the number of patients not seen at the proper time, or referral and admission rates during weekends. CONCLUSION: The Canadian Emergency Department Triage and Acuity Scale (CTAS) is adaptable to countries beyond Canada and can be implemented successfully. The applied CTAS triage system in Al-Yarmouk UCC in Riyadh, Saudi Arabia, is considered to be well applied. Overall, urgent cases have been seen by physicians in a timely manner according to the triage system, and there was no delay in the management of critical cases which need prompt attention.